INTROSYM : Reformulasi Stolen Asset Recovery dalam Sistem Pemeriksaan Delik Korupsi Sektor Swasta - Melta Setya Rahayu Pujianti; Fazal Akmal Musyarri; Paradisa Eksakta Gheosa (CV Rewang Rencang, 2020)
“Power tends to corrupt, and absolute power corrupts absolutely” is Lord Acton's adagium, in reflection of executive misconduct in the form of intervention in the independence of reported companies. In line with the thinking of Romli Atmasasmita who stated that the increasing number of corruption in the private sector was due to the unwillingness of witnesses in reporting the case. Supported by UGM's Economic Sciences Laboratory which said state losses due to private corruption reached 40.53%, the author initiated the idea of Integrated Proofing System (INTROSYM), which is a system of cracking down on integrated corruption cases involving companies that include the stages of reporting witnesses from insiders (whistleblowers). However, there are corrupt assets that are rushed abroad, especially to certain countries such as Switzerland. The country keeps assets secret so strictly that it is difficult to prove even though the party requesting the opening of the case and proof is the country where the asset owner. So that a special regulation is needed that can open transparency of proof of the assets of a company stored abroad. Stolen Asset Recovery (StAR) is a partnership between the World Bank and is a product of the United Nations of Drugs and Crime that implements UNCAC. StAR makes it easier for the state to open cases and prove the company's assets. So far, many countries have implemented STAR, but only applied to assets owned by individuals and state officials. So that StAR can be further optimized by applying it to assets owned by the company. It is expected that the enforcement of INTROSYM can reduce the crime of corruption in the private sector that is difficult to do and solve in the realm of Indonesian law.